(untitled) (Eurasian Research Bulletin, 2023)
This article outlines the importance of Jane Austen’s life and her legacy in world literature. Jane’s parents were very book-loving and enlightened people, the writer’s curiosity in writing fiction was appeared in her early age. Jane Austen (1775 - 1817) is an English author who reflected the reality of middle-class women at the beginning of the 19th century. This article is about one of Jane Austen’s famous works called "Pride and Prejudice".